1992
DOI: 10.1007/bf00146382
|View full text |Cite
|
Sign up to set email alerts
|

Iron miners ? A ten year follow-up

Abstract: 1167 workers of Lorraine (France) iron mines, a random sample of 5600 workers aged 35 to 55 years, at work in 1975 constituted the initial cohort that was examined twice at 5-year intervals after the first examination. A questionnaire on respiratory symptoms and smoking habits (MRC questionnaire) plus questions on the work history of each participant was completed, vital capacity (VC), forced expiratory volume in one second (FEV1.0), residual volume (RV) and fractional uptake of CO (FuCO) were measured at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Wollastonite is a fibrous monocalcium silicate mineral. In contrast, in a selected group of iron miners with normal chest radiographs, 30 generally negative associations between underground mining exposures and lung function were reported. However, because no comparison population was studied, the effect of exposure could only be evaluated by comparing underground miners to surface miners.…”
Section: Mineral Dustsmentioning
confidence: 65%
“…Wollastonite is a fibrous monocalcium silicate mineral. In contrast, in a selected group of iron miners with normal chest radiographs, 30 generally negative associations between underground mining exposures and lung function were reported. However, because no comparison population was studied, the effect of exposure could only be evaluated by comparing underground miners to surface miners.…”
Section: Mineral Dustsmentioning
confidence: 65%
“…In an interesting series of epidemiological studies, PAHs coated onto iron oxides were found to constitute one of the main suspected factors of the excessive mortality by lung cancer among iron-ore miners (Mur et al, 1987;Pham et al, 1992;Chau et al, 1993). In vivo experiments wherein benzo [a]pyrene (BaP), as a prototypical member of PAHs, was coated onto haematite (Fe 2 O 3 ), as iron oxide particles commonly encountered in occupational settings, have been used extensively to investigate the role of iron in lung pathogenesis (for a review and references, see Wolterbeek et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Diseases resulting from sulphur mining activities are common such as respiratory problems [1], tooth erosion [2], and also stress markers [3]. Long-term exposure to sulphate particles can cause respiratory diseases [4], [5] and even premature death.…”
Section: Introductionmentioning
confidence: 99%